Structure and spectroscopy of oxyluciferin, the light emitter of the firefly bioluminescence - Naumov, Pance; Ozawa, Yutaka; Ohkubo, Kei; Fukuzumi, Shunichi (American Chemical Society (ACS), 2009)
The crystal structures of the pure, unsubstituted firefly emitter oxyluciferin (OxyLH(2)) and its 5-methyl analogue (MOxyLH(2)) were determined for the first time to reveal that both molecules exist as pure trans-enol forms, enol-OxyLH(2) and enol-MOxyLH(2), assembled as head-to-tail hydrogen-bonded dimers. Their steady-state absorption and emission spectra (in solution and in the solid state) and nanosecond time-resolved fluorescence decays (in solution) were recorded and assigned to the six possible trans chemical forms of the emitter and its anions. The spectra of the pure emitter were compared to its bioluminescence and fluorescence spectra when it is complexed with luciferase from the Japanese firefly (Luciola cruciata) and interpreted in terms of the intermolecular interactions based on the structure of the emitter in the luciferase active site. The wavelengths of the emission spectral maxima of the six chemical forms of OxyLH(2) are generally in good agreement with the theoretically predicted energies of the S(0)-S(1) transitions and range from the blue to the red regions, while the respective absorption maxima range from the ultraviolet to the green regions. It was confirmed that both neutral forms, phenol-enol and phenol-keto, are blue emitters, whereas the phenolate-enol form is yellow-green emitter. The phenol-enolate form, which probably only exists as a mixture with other species, and the phenolate-enolate dianion are yellow or orange emitters with close position of their emission bands. The phenolate-keto form always emits in the red region. The concentration ratio of the different chemical species in solutions of OxyLH(2) is determined by several factors which affect the intricate triple chemical equilibrium, most notably the pH, solvent polarity, hydrogen bonding, presence of additional ions, and pi-pi stacking. Due to the stabilization of the enol group of the 4-hydroxythiazole ring by hydrogen bonding to the proximate adenosine monophosphate, which according to the density functional calculations is similar to that due to the dimerization of two enol molecules observed in the crystal, the phenolate ion of the enol tautomer, which is the predominant ground-state species within the narrow pH interval 7.44-8.14 in buffered aqueous solutions, is the most probable emitter of the yellow-green bioluminescence common for most wild-type luciferases. This conclusion is supported by the bioluminescence/fluorescence spectra and the NMR data, as well the crystal structures of OxyLH(2) and MOxyLH(2), where the conjugated acid (phenol) of the emitter exists as pure enol tautomer.